SONGS AS MEDIA TO IMPROVE STUDENTS’ ACHIEVEMENT IN UNDERSTANDING ENGLISH PRONUNCIATION (THE CLASSROOM ACTION RESEARCH OF EIGHT GRADERS AT SMP MUHAMMADIYAH 07 MEDAN - Khairunnisa, Windy; Sabila, Fadiyah Hani (BRIGHT VISION Journal of Language and Education, 2023)
Pronunciation is the  production  of  speech  sounds for  communication. For many students, the English speech sounds are confusing. There are many differences of pronunciation  between  English  and  Indonesian.  Therefore,  there  are  many students  of  Junior  High  School  especially  students  of  SMP  Muhammadiyah  07 Medan that pronounce   English   words   incorrectly.   This   study   was   conducted under   the consideration that pronouncing English words plays an important role. Most of the students may have problems to pronounce part since English is not our native language, although they get an English subject in their school and they can‟t master the English pronunciation well. The research was carried out through Classroom Action Research (CAR) and the sample of the research is the VIII-1 grader students of SMP Muhammadiyah 07 Medan. In collecting data, this research uses questionnaire, observation sheet, diary notes, test and photography. The students‟  achievement in the post test II & I is higher than that of the pre test with the mean score 82,70 > 76,09 > 69,83. In doing this study, the writer used an oral test method or sound of production. The action was done through teaching learning process. All of the teaching learning process were presented by the help of songs. After the treatment by using songs in each cycle, the students‟ achievement in pronouncing English words improved. It proven by the percentage of students‟ who get score up to 75 in pre-test and post-test I and post-test II. It was 20% students in pre-test, 44% students in post-test I, and 88% in post-test II. Based on this study, it was found that the use of songs in teaching English was effective and very beneficial to improve the students‟ pronunciation.